BRIDGING ISSUES OF STRESS AND MENTAL HEALTH IN THE WORKPLACE THROUGH ARTICLE WRITING IN ONLINE MASS MEDIA - Hakiki, Moh. Saiful; Putra, Riyan Sisiawan; Herlambang, Teguh; Karya, Denis Fidita; Adinugroho, Mukhtar (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
This community service activity discusses the issue and role of stress and mental health in the workplace and how writing articles in online mass media, such as Kumparan, can help overcome these issues. Stress, although often considered detrimental, can actually have a positive impact on an individual's performance and achievement if faced in the right levels. Studies show that appropriate pressure can motivate individuals to achieve high achievements. Stimuli and perceptions have a role in shaping individual attitudes and behaviors in the workplace. In addition to pressure levels, positive perceptions of organizational support impact job performance and satisfaction, while negative perceptions can lead to excess stress and burnout. Environmental, organizational, and individual factors influence perceptions of pressure or workload. Through writing articles in online mass media, this article explains how writing on platforms like Kumparan can be an effective tool in bridging stress and mental health issues in the workplace. This article not only provides information on the impact of stress and how to cope with it, but also encourages positive attitude and behavior change related to this issue. Article dissemination can be done through various channels, including one of them through social media, to reach a wider target audience. With a better understanding of the relationship between stimulus, perception, and pressure, this article helps in creating a balanced work environment and supports the well-being, productivity, and quality of life of employees. Therefore, the article has the potential to influence stress-related and mental health-related mindsets and practices in the workplace, as well as encourage better management in the context of Human Resource Management and Organizational Behavior.